Acción tutorial docente en la atención a los estudiantes con discapacidad intelectual grave de Educación General Básica - Huacón Pachay, Angie Stefani (2023)
Inclusive education aims at the existence of quality education for all. The teacher who is in charge of students with some type of disability faces important challenges in terms of their preparation and development of skills. The present study is focused on analyzing the influence of the teaching tutorial action to attend 6th grade EGB students with profound intellectual disabilities (DIG, as in Spanish) of the Unidad Educativa del Milenio IEC, school year 2022-2023. For this purpose, the theoretical framework of the research variables was systematized, and research tools were applied to determine the real situation of the teaching tutorial action towards students with DIG. The methods used were the analytical-synthetic, the inductive and the empirical, which allowed the study and assessment of the particularities of the variables. A mixed approach was also applied, which included the observation, the interview and the survey techniques, to a population of 35 6th grade EGB students, 35 parents, 3 teachers and 1 director of the Institution, with a sample not probabilistic. The results obtained confirmed the influence of the tutorial action in the attention to students with DIG, reflected in the insufficient participation of the teacher as a manager of the school improvement processes. Additionally, these results allowed us to propose a set of training workshops that strengthen the preparation of teachers in the field of tutorial action for the attention of students with DIG.